Investigation on Rock Strata Fracture Regulation and Rock Burst Prevention in Junde Coal Mine. (26th September 2021) - Wang, Fengnian; Li, Gan; Liu, Chi
Abstract : Through the establishment of structural mechanics model, this paper analyzes the fracture of super thick rock stratum. Through the model, it can be seen that the fracture of low-level super thick rock stratum produces large elastic energy release and dynamic load, which is easy to produce disasters such as rock burst. The numerical calculation shows that under the influence of low hard and thick rock stratum, the leading area of coal mine roadway will produce energy concentration, and the coal pillar will also produce energy accumulation. Thick rock stratum is in bending state and has large bending elasticity. Coal pillar has large compression elasticity, which is the main reason for rock burst. The accumulation of elastic properties of overburden and rock burst caused by coal pillar energy storage can be effectively controlled by using advanced presplitting blasting, coal seam drilling pressure relief, and strengthening support.